Flower-like calcium phosphoserine complex as biomimetic mineral with high bioactivity. Issue 13 (September 2020) - Zhou, Hong; Jiang, Ying-Ying; Tan, Shuo; Liu, Li-Jia; Yao, Qian-Ting; Xia, Yu-Jian; Fan, Yun-Shan; Hu, Jian-Ping; Zhou, Zi-Fei; Lu, Bing-Qiang; He, Shi-Sheng; Chen, Feng
Abstract: Biomineralization is a set of processes whereby living organisms generate hierarchically structured organic–inorganic materials. Studies on biomineralization not only elucidate the natural process of biomineral formation but also contribute to the development of functional biomaterials. However, the function of small molecules in the process has not been clarified. In this study, phosphoserine (PS) was used as a phosphorus source to prepare biomimetic minerals, and a new flower-like organic–inorganic complex of calcium PS (CaPS) was obtained. The CaPS samples were self-assembled plate-like crystals in the first 10 min. Then, over the next 5 h of the reaction, the plate-like crystals were broken down into fine granular nanoparticles. The chemical and thermal properties of CaPS were characterized, and the results indicated that the CaPS was or had a similar structure to Ca(C3 H6 NO6 P)·H2 O. X-ray absorption near edge structure (XANES) and extended X-ray absorption fine structure spectra (EXAFS) were obtained, which clearly revealed 6-fold-coordinated Ca-O bonds with lengths of 2.319 (±0.0147) Å, 2.358 (±0.0147) Å, and 2.435 (±0.0147) Å. Furthermore, the results of a CCK-8 assay indicated the high biocompatibility of CaPS. When the samples were co-cultured with mouse preosteoblast cells (MC3T3-E1), CaPS exhibited good bioactivity to promote the osteoblast differentiation of cells. Owing to its excellent chemical and biological properties, the as-prepared CaPS complex is promising for various biomedical applications.